Statins and New-Onset Diabetes Mellitus: LDL Receptor May Provide a Key Link - Yu, Qi; Chen, Ying; Xu, Cang-Bao (Frontiers in Pharmacology, 2017)
Numerous studies have noted that populations treated with statins have increased risk for new-onset diabetes mellitus; however, the underlying molecular mechanisms are not fully understood. Interesting, familial hypercholesterolemia patients with mutations in the low-density lipoprotein receptor (LDLR) gene are protected against diabetes mellitus, despite these patients being subjected to long-term statin therapy. Since the common pathway between familial hypercholesterolemia and statin therapy is LDLR-mediated cellular cholesterol uptake, the arising question is whether the LDLR plays an important role in the diabetogenic effect of statins. Indeed, given that statins can regulate the LDLR expression in liver and peripheral tissue, there is a possible mechanism that the increased LDLR causes cellular cholesterol accumulation and dysfunction in pancreatic islets, explaining why statins fail to increase the risk of diabetes mellitus in familial hypercholesterolemia (FH) patients. In this paper, with regarded to recent literatures, we highlight the role of LDLR in the pathophysiology of cholesterol-induced pancreatic islets dysfunction, which may provide the key link between statins treatment and the increased risk of new-onset diabetes mellitus.